2022
DOI: 10.3390/ijerph192214756
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Perceived Social Support on Mental Health and Life Satisfaction among Residents: A Cross-Sectional Analysis of 8500 Subjects in Taian City, China

Abstract: Several studies have explored the relationship between mental health and life satisfaction. However, few studies have clarified the mechanisms underlying the relationship between mental health and life satisfaction among a large sample of the whole population. The aim of this study was to explore the mediating role of perceived social support between mental health and life satisfaction among the residents in Taian City, China. A total of 8500 residents were included in the analysis. A descriptive analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…In this line other investigations found that mental health (evaluated by GHQ-12), successful coping, self-confidence and stress were inversely correlated to PSS ( Denche-Zamorano et al., 2022d ; Denche-Zamorano et al., 2022e ; Franco-García et al, 2023 ) in various populations. This is in line with the results of the present study and could suggest that higher PSS is associated with greater mental well-being ( Adamczyk & Segrin, 2015 ; Dong et al, 2022 ; Guo, Tan & Zhu, 2022 ; Singh, Verma & Lata, 2022 ). Furthermore, small inverse correlations were found among PSS and all the GHQ-12 items, which may indicate that greater PSS is associated with lower scores in the mental health variables derived from the GHQ-12, Similar results were found in a population of people with depression ( Denche-Zamorano et al., 2022d ), asthma ( Denche-Zamorano et al., 2022e ) and people with cancerous tumours ( Franco-García et al, 2023 ) where PSS had significant inverse correlations with the GHQ-12 items.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this line other investigations found that mental health (evaluated by GHQ-12), successful coping, self-confidence and stress were inversely correlated to PSS ( Denche-Zamorano et al., 2022d ; Denche-Zamorano et al., 2022e ; Franco-García et al, 2023 ) in various populations. This is in line with the results of the present study and could suggest that higher PSS is associated with greater mental well-being ( Adamczyk & Segrin, 2015 ; Dong et al, 2022 ; Guo, Tan & Zhu, 2022 ; Singh, Verma & Lata, 2022 ). Furthermore, small inverse correlations were found among PSS and all the GHQ-12 items, which may indicate that greater PSS is associated with lower scores in the mental health variables derived from the GHQ-12, Similar results were found in a population of people with depression ( Denche-Zamorano et al., 2022d ), asthma ( Denche-Zamorano et al., 2022e ) and people with cancerous tumours ( Franco-García et al, 2023 ) where PSS had significant inverse correlations with the GHQ-12 items.…”
Section: Discussionsupporting
confidence: 93%
“…Reducing psychological distress of people with anxiety may be key in order to decrease the health care costs derived from this disorder, especially given its prevalence in the Spanish adult population ( Villagrasa et al, 2019 ). Several studies support the potential effect of PA ( Harvey et al, 2010 :20; Herring, Lindheimer & O’Connor, 2014 ; Kandola et al, 2018 ; Lautenschlager et al, 2004 ; McDowell et al, 2019 ; Schuch et al, 2019 ; Stubbs et al, 2017 ) and good levels of PSS ( Adamczyk & Segrin, 2015 ; Dong et al, 2022 ; Guo, Tan & Zhu, 2022 ; Singh, Verma & Lata, 2022 ), improving mental health, and even the positive effect of greater PAL on PSS ( Kang, Park & Wallace, 2018 ; Yusuf et al, 2021 ), but cause–effect associations cannot be established due to the design of our study. Thus, it seems that disseminating the importance of good social support networks for people with anxiety and promoting the relevance of having a physically active lifestyle in this population is a relevant action that should be taken from the institutions.…”
Section: Practical Applicationsmentioning
confidence: 69%
See 1 more Smart Citation
“…In this sense, it helps to recognize and use various social support resources to protect themselves from general or emotional distress ( Wu et al, 2022 ), reducing mental health problems ( Rueger et al, 2016 ; Uchino et al, 2016 ; Hu et al, 2020 ). Similarly, Dong et al (2022) found that mental health is significantly related to perceived social support and life satisfaction; although after adjusting the control variables they found that perceived social support partially played a medium effect on mental health and life satisfaction.…”
Section: Discussionmentioning
confidence: 94%